Economic Analysis of Market Demand, Supply, and Opportunities for Pineapple in Manipur - Khapudang, Themshang; Dipak Kumar Bose; Laishram, Rabina (The Indian Journal of Agricultural Sciences, 2026)
Pineapple (Ananas comosus) is a crucial cash crop in the Indian state of Manipur. This study was carried out in 2024 in the Imphal-East, Senapati, and Kangpokpi districts to examine the market demand, supply trends, and opportunities for pineapple. A sample of four hundred and fifty respondents was randomly selected for the study. The findings indicated that the area under cultivation exhibited a Compound Annual Growth Rate (CAGR) of -1.87, with productivity (yield) increasing from an initial value of 9.95 MT/ha to a final value of 11.08 MT/ha with a CAGR of 1.08%. The marketing channel results for Channel I (Producer → Consumer) was the most efficient, with a Producer-Share in the Consumer’s Rupee (PSCR) of 84.00% and a Modified Marketing Efficiency (MME) of 6.25. The SWOT analysis revealed that the majority (94.89%) of the respondents had traditional, chemical-free farming practices, the majority (86.89%) lacked transportation, the majority (97.33%) of the respondents stated their eagerness to undergo the value-addition process using juice and canning units, and the majority (90.89%) of the respondents had regional bandh/blockades as their major strengths, weaknesses, opportunities, and threats, respectively. This study highlights the necessity of local processing systems and supply chains based on collaboration to improve the returns of growers and capitalize on the un-utilized industrial capacity of the state.